Effects of Allopurinol on the Progression of Chronic Kidney Disease - Badve, Sunil V; Pascoe, Elaine M; Tiku, Anushree; Boudville, Neil; Brown, Fiona G; Cass, Alan; Clarke, Philip; Dalbeth, Nicola; Day, Richard O; de Zoysa, Janak R; Douglas, Bettina; Faull, Randall; et al. (The New England journal of medicine, 2020)
This randomized trial assessed whether urate-lowering treatment with allopurinol could attenuate eGFR decline in at-risk patients with stage 3 or 4 chronic kidney disease. Allopurinol did not slow the decline in eGFR as compared with placebo.